Determination of Iodine Value in Hydrogenated Oils: Comparison of Titration and Gas Chromatography with Flame‐Ionization Detection Methodologies. Issue 7 (19th September 2018) - Kotoski, Shaun P.; Srigley, Cynthia T.
Abstract: The United States Food and Drug Administration (FDA) recently issued its final determination that partially hydrogenated oils (PHO) are no longer generally recognized as safe (GRAS) for any use in human food. Consequently, the discrimination between PHO and fully hydrogenated oils (FHO), which is achieved by the iodine value (IV), has become an important regulatory issue. This study compared American Oil Chemists' Society (AOCS) and International Organization for Standardization (ISO) titration and gas chromatography with flame‐ionization detection (GC‐FID) methodologies for the determination of IV in seven samples of hydrogenated oil, namely coconut, cottonseed ( n = 2), palm kernel, palm stearine, and soybean ( n = 2) oils. Titrations produced statistically higher IV determinations than those achieved by GC‐FID, for all samples except the FH coconut oil. The unsaponifiable matter content of the hydrogenated oils, which varied from 0.15% to 0.47% of total fat, likely contributed modest increases to the IV by titration. Both methodologies were prone to issues at low IV ( 4), with titrations showing greater variability, and GC‐FID being susceptible to incomplete separation, identification, and quantification of all unsaturated fatty acids. The variability observed with titrations could be minimized by careful execution of the titration protocol. Although both approaches successfully discriminated PHO and FHO in the test materials, at low IV ( 4), titration is the most accurate method for determining the IV, and the only approach that has been validated in oils with a very low IV (<1).